The Changing Academic Profession in Japan
VIII, 270 p. 23 illus.
Keywords: This volume provides an empirical and qualitative analysis of the nature and extent of the Japanese academic profession, with a special focus on the changes that occurred in the period between 1992 and 2007. Based on responses to two comprehensive surveys administered to faculty samples with a similar questionnaire, the book presents key aspects of the academic activities and views of Japanese faculty members. Divided into five sections, the book describes the changing social, economic and educational environment, academic organization and life, productivity, as well as the effects of the profession on society. The last section describes the Japanese academic profession as observed from the USA and Asia. In addition to its focus on empirical analysis, the book makes use of historical and comparative perspectives to explore the various aspects of the changes that have occurred in the academic profession in this non-English-speaking country.